Pengaruh Kepemimpinan dan Kepuasan Kerja Terhadap Kinerja Dosen di Universitas Majalengka, Jawa Barat - Dita Cucu Kartika; Maruf Akbar; Rugaiyah Rugaiyah (Universitas Mathla'ul Anwar Banten, 2018)
EFFECT OF EMPOWERMENT AND JOB SATISFACTION TOWARD JOB PERFORMANCE OF LECTURER IN MAJALENGKA UNIVERSITY, WEST JAVA. The objective of this research is to understand comprehensively the effect of empowerment and job satisfaction toward job performance of lecturer in Majalengka University, West Java. A survey method with path analysis techniques was used by applying a questioner as a research instrument. 80 responders were involved by sending their feedback within the questioner. Those responders were decided using simple random sampling among all lecturers that working at the Majalengka University. The data result, analysis and interpretation reveal that (1) empowerment has a direct positive effect toward job performance, (2) job satisfaction has a direct positive effect toward job performance, (3) empowerment has a direct positive effect toward job satisfaction.